Identidades de género, feminismo, sexualidad y amor: Los cuerpos como agentes - Esteban Galarza, Mari Luz (Política y Sociedad, 2009)
This article analyzes, on the one hand, the influence of sexuality and love in the construction and change of gender identity as well as the interrelations between the options and preferences of the persons and his/hers concrete sexual and affectionate practices. On the other hand, from our point of view gender, corpority, sexuality and love are ways of “being” in this world and also conceptuals frames and experiences separates but, at the same time, narrowly inter related. The analisys is based on the descriptions given by feminist women interviewed in the frame of an ethnographic study of romantic love.